87.5k views
3 votes
Cos square there + cos square theta multiply cot square theta = cot square theta​

1 Answer

3 votes

Step-by-step explanation:

We need to prove that :
\cos^2\theta+\cos^2\theta {\cdot} \cot^2\theta=\cot^2\theta

Taking LHS :
\cos^2\theta+\cos^2\theta {\cdot} \cot^2\theta

Taking
\cos^2\theta common as follows :


\cos^2\theta(1+ \cot^2\theta) ...(1)

We know that :


cosec^2\theta-\cot^2\theta=1\\\\cosec^2\theta=1+\cos^2\theta ....(2)

Use equation (2) in equation (1) as follows :


\cos^2\theta{\cdot} cosec^2\theta

We know that :
cosec\theta=(1)/(\sin\theta)

So,


\cos^2\theta{\cdot} (1)/(\sin^2\theta)\\\\=\cot^2\theta

=RHS

Hence, LHS = RHS

User Theo Sweeny
by
4.6k points